Choice Behaviour and Verbal Behaviour: A Critical Assessment of their Relevance for Practical Policy - Bernard M.S. van Praag; P. Frijters (Tinbergen Institute, 1997)
In this paper we review five different methods used to determine the welfareeffects of policy changes: hedonic price analysis, contingent valuation, conjoint measurement, the Income Evaluation Approach, and the Cantril approach. In the first three approaches, an attempt is made to discover the implicit prices which individuals use to value several amenities. Such analyses are in practice frequently used to discover the value of a warm climate, the cost of noise pollution, the value of an aspect of a musical performance, the importance of a particular trait of a job applicant, etc.In short, the first three approaches are used to discover prices for goods forwhich there are no directly observable prices. These approaches can be used to find the money-equivalent amount that policy changes are worth to different individuals. They can however not be used for welfare comparisons as they do not tell ushow much welfare different individuals derive for each unit of money.The other methods are based on individual's valuation of their own income ortheir life as a whole. These two approaches can, and have been, used to find implicit prices, but they also have a much wider use. In theory and in practice, they can be used to make welfare statements about proposed or actualised policy changes.
Keywords: 330; Verhaltensökonomik; Wirtschaftspolitik; Theorie